Diversity and Distribution of Phenol Oxidase Producing Fungi from Soda Lake and Description of Curvularia lonarensis sp. nov. - Sharma, Rahul; Prakash, Om; Sonawane, Mahesh S.; Nimonkar, Yogesh; Golellu, Priyanka B.; Sharma, Rohit (Frontiers in Microbiology, 2016)
Soda lake is hyper alkaline and saline habitat located in closed craters with high evaporation rate. In current study fungal diversity from water and sediment samples of a soda lake (Lonar lake) located in Buldhana district of Maharashtra, India was investigated using extensive culturomics approach and mimicking the natural conditions of Lonar lake in culture media. A total of 104 diverse isolates of extremophilic fungi were recovered from this study and phylogenetically characterized by internal transcribed spacer (ITS) region sequencing. In addition, due to important role of phenol oxidase and peroxidase in degradation of toxic phenol, lignin, etc., all isolated pure cultures were also screened for extracellular phenol oxidase and peroxidase production potential. Diversity analysis indicated that different groups of extremophilic fungi are present in the water and sediment samples of Lonar lake. A total of 38 species of fungi belonging to 18-different genera were recovered. Out of 104 isolates 32 showed ≤ 97% sequences similarity, which were morphologically different and could be potential novel isolates of extremophilic fungi. However, out of 104 isolates only 14 showed the extracellular phenol oxidase production potentials at alkaline pH. Curvularia sp. strain MEF018 showed highest phenol oxidase production at alkaline condition and had low sequence similarity with previously characterized species (96% with Curvularia pseudorobusta). Taxonomic characterization (morphological and physiological) and multi locus sequence analysis (MLSA) using combined alignment of ITS-LSU-gpd of strain MEF018 showed that it is a novel species of the genus Curvularia and hence proposed as Curvularia lonarensis sp. nov.